2013
DOI: 10.2147/ijn.s39456
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the effects of graphene platelets on glioblastoma multiforme cells

Abstract: Abstract:Graphene is a single atom-thick material with exciting potential. It can be used in many fields, from electronics to biomedicine. However, little is known about its toxicity and biocompatibility. Herein, we report a study on the toxicity of graphene platelets (GPs) by examining the influence of GPs on the morphology, mortality, viability, membrane integrity, and type of cell death of U87 and U118 glioma cells. It was found that graphene is toxic to glioma cells, but it activated apoptosis only in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…To some extent, the chemical properties of graphene are similar to those of graphite, owing to the fact that, in both cases, C-atoms are sp 2 hybridized. Jaworski et al [ 39 ] published their work on the influence of graphene platelets on the morphology, mortality, viability, membrane integrity and type of cell death. Our studies on graphite partially confirmed their results in the case of the MTT test and morphology observations of glioblastoma cells treated with graphene.…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, the chemical properties of graphene are similar to those of graphite, owing to the fact that, in both cases, C-atoms are sp 2 hybridized. Jaworski et al [ 39 ] published their work on the influence of graphene platelets on the morphology, mortality, viability, membrane integrity and type of cell death. Our studies on graphite partially confirmed their results in the case of the MTT test and morphology observations of glioblastoma cells treated with graphene.…”
Section: Discussionmentioning
confidence: 99%
“…al. have reported the interactions of graphene platelets with human glioblastoma U87 and U118 cells [68]. After 24 hours of incubation with 100 µg/ml graphene, 42% and 52% cell mortality was observed for U87 and U118 cells, respectively.…”
Section: In Vitro Toxicitymentioning
confidence: 99%
“…Other cancer types such as Burkitt's lymphoma 33 , colon cancer 34 , 70 , 71 , 78 , 91 , prostate cancer 35 , 64 , 87 , lung cancer 43 , 56 , 63 , 76 , 80 , 87 , skin cancer 57 , 60 , brain cancer 20 , 38 , 46 - 48 , 61 , 62 , glioma 90 and glioblastoma 72 were studied under different drug treatment conjugated with graphene or graphene oxide.…”
Section: Drug and Gene Deliverymentioning
confidence: 99%
“…On the other hand, specific toxic effects of graphene on cancer cells could represent a positive point. Indeed, many reports have shown that this function of graphene could be useful in possible future therapeutic applications 20 , 21 , for example as an inhibitor of cancer cell metastasis 22 . Furthermore, different anticancer biomolecules such as siRNA, DNA and other drugs can be loaded onto the graphene surface for gene silencing and transfection, drug delivery and many other cancer therapy applications 23 .…”
Section: Introductionmentioning
confidence: 99%